Fish oil supplementation, physical activity and risk of incident Parkinson’s disease: results of longitudinal analysis from the UK Biobank - Lin, Fabin; Shi, Yisen; Zheng, Jiayi; Li, Yueping; Chen, Xuanjie; Zou, Xinyang; Hong, Yi; Chen, Ke; Zeng, Yuqi; Ye, Qinyong; Chen, Xiaochun; Chen, Xinyan; et al. (Frontiers in Aging Neuroscience, 2024)
Objective Evidence on the individual and combined relationship of physical activity (PA) and fish oil supplement use on the incidence of Parkinson’s disease (PD) risk remains lacking. Materials and methods This UK population-based prospective cohort study, involving 385,275 UK Biobank participants, collected PA and fish oil supplement data via touchscreen questionnaires. Using Cox proportional hazards models and restricted cubic splines to examined the associations between use of fish oil supplements, PA and PD risk. Results During a median 12.52-year follow-up, 2,131 participants incident PD. Analysis showed that fish oil supplement users had a lower PD risk [hazard ratio (HR), 0.89; 95% confidence interval (CI), 0.82–0.98]. The adjusted HRs for the PD incidence were 0.96 (95% CI, 0.95–0.98) for total PA; 0.93 (95% CI, 0.90–0.96) for moderate PA; 0.95 (95% CI, 0.91–0.99) for vigorous PA and 0.93 (95% CI, 0.89–0.98) for walking activity. Significant interactions were found between fish oil supplement use and total PA (P for interaction = 0.011), moderate PA (P for interaction = 0.015), and walking activity (P for interaction = 0.029) in relation to PD incidence. Conclusion Both fish oil supplement use and PA were associated with a reduced risk of PD, and the effect of PA in reducing the risk of PD was more pronounced when fish oil supplement was used.